Necrotizing Fasciitis in a Pediatric Patient Caused by Lancefield Group G Streptococcus: Case Report and Brief Review of the Literature. (27th December 2011) - Rausch, John; Foca, Marc
Abstract : We report a case of necrotizing fasciitis with an accompanying toxic shock syndrome caused by Group G Streptococcus in a pediatric patient with a lymphatic malformation. Pediatricians need to be aware of the possibility of such infections, especially in those with vascular/lymphatic malformations, as early treatment is critical for survival.